1995
DOI: 10.1007/978-1-4684-1572-8
|View full text |Cite
|
Sign up to set email alerts
|

Physical Metallurgy of Refractory Metals and Alloys

Abstract: All rights reservedNo part of this publication may be reproduced in any form without written permission from the publisher PREFACE TO THE AMERICAN EDITIONThe principal reasons which induced the authors to write this book and the features of the book are set forth in the preface to the Russian edition.That section of the science of metals which in Russian is called "metallovedenie" or the "physical chemistry of metals" is generally referred to in scientific and technical literature published in the English lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 29 publications
0
17
0
2
Order By: Relevance
“…Analyzing the data of Table 1 we will see that the degree of deformation affects the plasticity of the extruded rods more considerably than their strength. The mechanism of plastic deformation of refractory b.c.c, metals (Mo, W) is known [2] to depend on the crystallographic orientation of the specimens relative to the direction of the deformation. In this connection it seemed expedient to study the textural state of the specimens.…”
Section: O E R S H O V Amentioning
confidence: 99%
“…Analyzing the data of Table 1 we will see that the degree of deformation affects the plasticity of the extruded rods more considerably than their strength. The mechanism of plastic deformation of refractory b.c.c, metals (Mo, W) is known [2] to depend on the crystallographic orientation of the specimens relative to the direction of the deformation. In this connection it seemed expedient to study the textural state of the specimens.…”
Section: O E R S H O V Amentioning
confidence: 99%
“…The temperature in the region of 1250 to 1450°C is maintained in elements of the SF. The ratio of the working temperature to the melting point is equal to 0.7-0.8, which makes it necessary to perform a calculation for creep [1].Creep of platinum alloys has been widely investigated by foreign and domestic specialists [2][3][4]. It was found that the creep curves of platinum alloys are similar to the creep curves of pure metals.…”
mentioning
confidence: 99%
“…Using the theory of aging in [1, 6,7] and considering the results of the experimental studies on creep of platinum alloys in [2,4], we obtain the following dependence of the intensity of creep deformation ε i * in steady-state creep on the intensity of stress σ i and time t:…”
mentioning
confidence: 99%
See 2 more Smart Citations